FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN OUTPUT SEKTOR PERTANIAN DI SUMATRA SELATAN - Syamsurijal Syamsurijal (Jurnal Ekonomi Pembangunan, 2007)
The purpose of this study is to kow factors that affect growth rate of production of agricultural sector in South Sumatera province. It is assumed that total factor productivity, capital, and labor determine the growth rate of output of the sector. A Cobb-Douglas production function is used to determine those factors that may influence the growth rate of output of agricultural sector. The results indicate that total factor productivity has a positive dominant effect on growth rate of production of agricultural sector, while capital and labor have a negative effect. Therefore, it suggests that the growth rate could be raised if there is a reduction in the use of capital and labor. However care should be taken because agricultural sector play an important role in absorbing labor force in South Sumatera province. Key Words: Total Factor Productivity, Economic Growth, Agricultural sector